Genome re-assignment of Arachis trinitensis (sect. Arachis, Leguminosae) and its implications for the genetic origin of cultivated peanut - Robledo Dobladez, Germán Ariel (2010)
The karyotype structure of Arachis trinitensis was studied by conventional Feulgen staining, CMA/DAPI banding and rDNA loci detection by fluorescence in situ hybridization (FISH) in order to establish its genome status and test the hypothesis that this species is a genome donor of cultivated peanut. Conventional staining revealed that the karyotype lacked the small "A chromosomes" characteristic of the A genome. In agreement with this, chromosomal banding showed that none of the chromosomes had the large centromeric bands expected for A chromosomes. FISH revealed one pair each of 5S and 45S rDNA loci, located in different medium-sized metacentric chromosomes. Collectively, these results suggest that A. trinitensis should be removed from the A genome and be considered as a B or non-A genome species. The pattern of heterochromatic bands and rDNA loci of A. trinitensis differ markedly from any of the complements of A. hypogaea, suggesting that the former species is unlikely to be one of the wild diploid progenitors of the latter. © 2010, Sociedade Brasileira de Genética.